Vibrational Spectroscopy, Quantum Computational and Molecular Docking Studies on 2-[(1H-Benzimidazol-1-yl)-methyl]benzoic Acid - Ghazala Khanum; Arif Ali; Sadiya Shabbir; Aysha Fatima; Norah Alsaiari; Yasmeen Fatima; Musheer Ahmad; Nazia Siddiqui; Saleem Javed; Mayank Gupta (Crystals, 2022)
Experimental and theoretical investigations on the optimized geometrical structure, electronic and vibrational features of 2-[(1H-benzimidazol-1-yl)-methyl]benzoic acid are provided using the B3LYP/6-311++G(d,p) basis set. The Vibrational Energy Distribution Analysis (VEDA) program was used to perform the vibrational assignments and calculate the Potential Energy Distribution (PED). The acquired FT-IR and FT Raman data were used to complete the vibrational assignment and characterization of the compound fundamental modes. Theoretical and actual NMR chemical shifts were found to be quite similar. The UV-vis spectrum of 21HBMBA, as well as effects of solvents, have been investigated. The calculated HOMO and LUMO energies reveal that charge transfer happens within the molecule and MEP surface to be a chemically reactive area appropriate for drug action. Furthermore, a thorough examination of Non-Bonding Orbitals, excitation energies, AIM charges, Fukui functions and the Electron Localization Function (ELF) is carried out. The research is also expanded to compute first-order hyperpolarizability and forecast NLO characteristics. The details of the docking studies aided in the prediction of protein binding.